Collateral contamination concomitant to the polonium-210 poisoning of Mr Alexander Litvinenko. (14th September 2017) - Harrison, John; Smith, Tracy; Fell, Tim; Smith, Jenny; Ham, George; Haylock, Richard; Hodgson, Alan; Etherington, George
Abstract: Mr Litvinenko died on 23 November 2006, having been poisoned with polonium-210 on 1 November, with evidence of a previous poisoning attempt during October 2006. Measurements of 210 Po in urine samples were made for a large number of people to determine whether they may have been contaminated. In the majority of cases, measured levels were attributable to the presence of 210 Po from normal dietary sources. For a small number of cases, elevated levels provided evidence of direct contamination associated with the poisonings. For one individual, while estimated doses were below thresholds for irreversible organ damage, a notably increased risk of cancer can be inferred. The use of the chelating agent, unithiol, to increase 210 Po excretion in this case was only moderately effective in reducing doses received.